2016
DOI: 10.2147/copd.s111573
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator response of advanced lung function parameters depending on COPD severity

Abstract: BackgroundCOPD is defined as partly irreversible airflow obstruction. The response pattern of bronchodilators has not been followed in advanced lung function parameters.PurposeThe aim of this study was to investigate bronchodilator response pattern in advanced lung function parameters in a continuous fashion along forced expiratory volume in 1 second (FEV1) percent predicted (%p) in COPD patients and controls.Patients and methodsEighty-one smokers/ex-smokers (41 controls and 40 COPD) performed spirometry, body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…Accordingly, (iii) BDR is distinctive for each single parameter. In consequence, our study shows that (iv) BDR largely depends on the type and degree of pre-test dysfunction 49 and, therefore, the magnitude of the BDR was greater than expected, and as previously reported. 22 , 49–51 Unmistakably, it must be recognized that the overwhelming belief that COPD patients mostly present with an irreversible flow-limitation, is only based on the worldwide approach that reversibility mostly was assessed by simple spirometric measurements.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Accordingly, (iii) BDR is distinctive for each single parameter. In consequence, our study shows that (iv) BDR largely depends on the type and degree of pre-test dysfunction 49 and, therefore, the magnitude of the BDR was greater than expected, and as previously reported. 22 , 49–51 Unmistakably, it must be recognized that the overwhelming belief that COPD patients mostly present with an irreversible flow-limitation, is only based on the worldwide approach that reversibility mostly was assessed by simple spirometric measurements.…”
Section: Discussionsupporting
confidence: 88%
“… 45–49 Jarenbäck et al investigated the BDR based on advanced lung function parameters and brought to light that apart from flow response, also volume response, or a combination of both, have to be identified, if BDR is to be correctly assessed in COPD. 49 Topalovic et al and Borrill et al demonstrated that the specific airway conductance (sG aw ) could be a significant factor to differentiate asthma from COPD, 45 , 47 and regarding BDR, Saito et al showed that sG aw is a more sensitive measurement for detecting lung function changes in COPD patients than the more commonly used FEV 1 . 48 However, to our knowledge, none of these author groups evaluated measurements assessing airway dynamic parameters by the plethysmographic integral method featuring the parameters sR eff , sG eff , and sWOB.…”
Section: Discussionmentioning
confidence: 99%
“…Jarenbäck et al performed spirometry and body plethysmography at baseline and after bronchodilator. Their results stated that volume response does not follow the flow response (FEV1) and flow parameters were more significant in less advanced stage, whereas parameters reflecting volume response (FVC) were more prominent in patients with more severe stages of COPD [36]. Barjaktarevic et al showed that mild COPD (GOLD I) was characterized by greater BDR in terms of FEV1 than BDR in terms of FVC (35.6% vs 19.2%), a difference that was less marked in GOLD grades II and III.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchodilator response of advanced lung function parameters depends on COPD severity. 17 In more severe cases of COPD patients, FVC remarkably rises after bronchodilator administration whereas FEV1 remains substantially constant, 7 isolated volume response to bronchodilators is a characteristic of severe emphysema in COPD patients. 6,9,18 In other words, FVC responders may suffer from more severe airway hyperresponsiveness, airway obstruction, and emphysema.…”
Section: Discussionmentioning
confidence: 99%